2021
DOI: 10.1007/s10741-021-10135-4
|View full text |Cite|
|
Sign up to set email alerts
|

Polypharmacy definition and prevalence in heart failure: a systematic review

Abstract: Polypharmacy and heart failure are becoming increasingly common due to an ageing population and the rise of multimorbidity. Treating heart failure necessitates prescribing of multiple medications, in-line with national and international guidelines predisposing patients to polypharmacy. This review aims to identify how polypharmacy has been defined among heart failure patients in the literature, whether a standard definition in relation to heart failure could be identified and to describe the prevalence. The He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 54 publications
3
40
0
Order By: Relevance
“…The study has proved that there was little difference between the 2017 Chinese and 2019 AGS/Beers criteria ( Tian et al, 2022 ), so the Beers criteria was also capable for Chinese. Our results are comparable to the PIM rate of ( Beezer et al, 2022 ), who reported that the incidence of PIM was 61.1% during hospitalization in older patients with heart failure. Still, the PIM after discharge was higher, which was 64.0%.…”
Section: Discussionsupporting
confidence: 89%
“…The study has proved that there was little difference between the 2017 Chinese and 2019 AGS/Beers criteria ( Tian et al, 2022 ), so the Beers criteria was also capable for Chinese. Our results are comparable to the PIM rate of ( Beezer et al, 2022 ), who reported that the incidence of PIM was 61.1% during hospitalization in older patients with heart failure. Still, the PIM after discharge was higher, which was 64.0%.…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence estimates reported in this review are substantially higher than the general population including cohorts at high risk of experiencing polypharmacy such as elderly (Veehof et al, 2000), patients with chronic liver disease (Danjuma et al, 2022a), and people living with HIV (Danjuma et al, 2022b). However, the estimates were comparable to other populations that are also known to be more exposed to polypharmacy such as heart failure patients (Beezer et al, 2021).…”
Section: Discussionsupporting
confidence: 68%
“…Polypharmacy is associated with worse outcomes, including falls, disability, and hospitalization. 25 This additive burden in combination with social isolation may serve as a reason for discontinuation of medication.…”
Section: Discussionmentioning
confidence: 99%